Spin excitations in metallic kagome lattice FeSn and CoSn - Yaofeng Xie (Nature Portfolio, 2021)
By exploiting the geometric frustration of a kagome crystal lattice, it is possible to enhance electron localisation and engineer exotic electronic structures such as electronic flat bands. Here, the authors use inelastic neutron scattering to investigate the evolution of spin excitations modes for FeSn and CoSn, finding that an anomalous flat mode actually arises from the material used to fix the sample to the aluminium holder for analysis instead of the expected magnetic flat bands.